2020
DOI: 10.1101/2020.05.17.100909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does chronic systemic injection of the DREADD agonists clozapine-N-oxide or compound 21 change behavior relevant to locomotion, exploration, anxiety, and depression in male non-DREADD-expressing mice?

Abstract: Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) are a chemogenetic tool commonly-used to manipulate rodent brain circuit activity. The most widely-used synthetic ligand for DREADDs is Clozapine-N-oxide (CNO). However, CNO is back-metabolized to clozapine, which itself activates numerous endogenous receptors and therefore may influence rodent behavior. To eliminate potential off-target effects of CNO, a new DREADD agonist, Compound 21 (C21), has been proposed as an alternative as it lacks a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is also beneficial for neuroscience research aimed at long-term control of neuronal activity in freely-moving animals without restraint or stress. However, recent studies have reported that CNO has low permeability into the brain, and that its metabolite, clozapine, activates not only DREADDs but also endogenous receptors and transporters, leading to potential off-target effects (Gomez et al, 2017;Tran et al, 2020). To circumvent this issue, alternative selective DREADDs agonists have been explored and validated (Bonaventura et al, 2019;Weston et al, 2019;Nagai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is also beneficial for neuroscience research aimed at long-term control of neuronal activity in freely-moving animals without restraint or stress. However, recent studies have reported that CNO has low permeability into the brain, and that its metabolite, clozapine, activates not only DREADDs but also endogenous receptors and transporters, leading to potential off-target effects (Gomez et al, 2017;Tran et al, 2020). To circumvent this issue, alternative selective DREADDs agonists have been explored and validated (Bonaventura et al, 2019;Weston et al, 2019;Nagai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…one hour before IA training to transiently silence neuronal activity in the ACC (Fig. 7A) (Jendryka et al, 2019; Luo et al, 2021; Tran et al, 2020). In addition to hM4Di, the AAV-hSyn-hM4D(Gi)-mCherry viral construct expresses the fluorescent protein mCherry in neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been suggested that the in vivo activation of DREADDs after CNO administration is not due to CNO, which is poorly penetrant to the brain, but rather a metabolic production of clozapine. 21 -24 Deciphering which effects are DREADD-mediated, and which are due to off target effects of DREADD agonists is an important consideration …”
Section: Pharmacology Of Chemogenetic Agonistsmentioning
confidence: 99%